Sektor Kunci dalam Perekonomian Kabupaten Sanggau: Analisis Input-Output - Suratman, Eddy; Irawan, Thomas Tony (UI Scholars Hub, 2009)
This research is aimed to investigate the key sectors in the economy of Sanggau District. This research is descriptive and is using input-output analysis to find out the multiplier of economic sectors. In addition we also investigate the linkage among economic sectors, which are measured by backward and forward linkage indexes. The finding of this research shows that there are two sectors being the key namely the processing industry and transportation and communication sectors with backward and forward linkage indexes above the average level of the other sectors. Agriculture were found to be the sector with the biggest employment absorption. Based on this finding, the development policy strategies should be directed toward the policy that creates maximum economy, particularly in the sectors of processing industry and transportation and communication. As it will create a better distribution of job vacation among sectors in Sanggau District.